2017
DOI: 10.1371/journal.pone.0181010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress, fear and anxiety on the nociceptive responses of larval zebrafish

Abstract: Both adult and larval zebrafish have been demonstrated to show behavioural responses to noxious stimulation but also to potentially stress- and fear or anxiety- eliciting situations. The pain or nociceptive response can be altered and modulated by these situations in adult fish through a mechanism called stress-induced analgesia. However, this phenomenon has not been described in larval fish yet. Therefore, this study explores the behavioural changes in larval zebrafish after noxious stimulation and exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 63 publications
(103 reference statements)
1
46
0
Order By: Relevance
“…Evidence for stress-induced analgesia has also been gathered in teleost fishes. In these studies, a stressful event before noxious stimulation prevents the associated behavioral and physiological responses (3,5,10,80,87). The impact of stress can be reversed by the injection of naloxone, an opioid antagonist (10).…”
Section: Fishes: Petromyzontids Elasmobranchs and Teleostsmentioning
confidence: 99%
“…Evidence for stress-induced analgesia has also been gathered in teleost fishes. In these studies, a stressful event before noxious stimulation prevents the associated behavioral and physiological responses (3,5,10,80,87). The impact of stress can be reversed by the injection of naloxone, an opioid antagonist (10).…”
Section: Fishes: Petromyzontids Elasmobranchs and Teleostsmentioning
confidence: 99%
“…Empirical studies in fishes have also confirmed the presence of nociceptors, demonstrating their properties are very similar to those found in humans and other mammals (Ashley et al ., , ; Mettam et al ., ; Sneddon, , , ). Studies in fishes have demonstrated changes in brain activity during noxious stimuli (Dunlop & Laming, ; Nordgreen et al ., ; Reilly et al ., ; Sneddon, ) and recorded adverse changes in behaviour and physiology during noxious treatments (Dunlop et al ., ; Maximino, ; Mettam et al ., ; Reilly et al ., ; Roques et al ., ; Sneddon, ; Sneddon et al ., , ; White et al ., ) all of which can be prevented by analgesics known to be effective in relieving pain in mammals (Lopez‐Luna et al ., , , , ; Mettam et al ., ; Newby et al ., ; Nordgreen et al ., ; Schroeder & Sneddon, ; Sneddon, , ; Taylor et al ., ). This empirical evidence taken together supports the idea that fishes may experience pain.…”
Section: Do Fishes Experience Pain?mentioning
confidence: 99%
“…Opioids inhibit neurotransmitter release pre‐synaptically thereby blocking nociceptors but these drugs also block central transmission. Several studies have shown morphine is an effective analgesic in O. mykiss (Baker et al ., ; Jones et al ., ; Sneddon, ) and other species ( e.g ., goldfish Carassius auratus (L. 1758); Nordgreen et al ., ; D. rerio , Lopez‐Luna et al ., ,b,c,d; Magalhaes et al ., ; Schroeder & Sneddon, ; Taylor et al ., ). Morphine has a pharmocokinetically similar action in fishes compared with mammals, however, morphine persists for a prolonged period after administration due to slower excretion rates (half‐life 37 h; Newby et al ., , ).…”
Section: Common Considerations For Laboratory and Field Studiesmentioning
confidence: 99%
See 2 more Smart Citations